Animal Domestication 2019
DOI: 10.5772/intechopen.78752
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Domestication on Fish Behaviour

Abstract: Domestication is a process by which humans select some phenotypes of wild animal species (i.e., morphological traits or growth), but as all traits are linked, the selection of a particular one has consequences on others. In that context, behavioural traits may be affected by human selection. In this chapter, through classical behavioural traits, such as swimming capacities, foraging, social interactions, or reproduction, and also personality or cognitive abilities, what domestication modifies in fish behaviour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 96 publications
0
21
0
Order By: Relevance
“…For most livestock species, it is thought that the early stages of domestication involved unconscious selection for behavioral traits (e.g., for tameness and reduced aggression), followed by selection focused on breeding objectives (Gregory, 2009). In fish, behavioral traits such as swimming capacities, foraging, social interactions, reproduction, or personality and cognitive abilities, are also modified by domestication (Pasquet, 2018). In the present study we identified the genes robo1 and dcdc2 which are associated to complex cognitive acquired skills, including spoken and written language in human (Mozzi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For most livestock species, it is thought that the early stages of domestication involved unconscious selection for behavioral traits (e.g., for tameness and reduced aggression), followed by selection focused on breeding objectives (Gregory, 2009). In fish, behavioral traits such as swimming capacities, foraging, social interactions, reproduction, or personality and cognitive abilities, are also modified by domestication (Pasquet, 2018). In the present study we identified the genes robo1 and dcdc2 which are associated to complex cognitive acquired skills, including spoken and written language in human (Mozzi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…We found several genes and enriched terms associated with behavior. For example, we found GO terms related to cognition (GO:0050890) and learning (GO:0007612), traits which have been reported to be impacted by the effect of domestication of fish 67 .…”
Section: Signatures Of Selectionmentioning
confidence: 93%
“…Some species that have been more intensely domesticated, under controlled artificial selection for growth or not, stay near the water surface rather near the bottom of the water column (Reinhardt et al 2001;Robison & Rowland 2005), which in turn improves their feeding efficiency (Thodesen et al 1999;S anchez et al 2012). Changes in social behaviour, for example shoaling, would be an additional behavioural cause of the higher growth in domesticated fish (Wright et al 2006;Pasquet 2019), potentially due to a higher homogeneity of age and size in domesticated fish (Ruzzante & Doyle 1991. This change in the structure of the social group may induce modifications of aggressiveness and hierarchy between individuals (Swain & Riddell 1990;Ruzzante & Doyle 1993;Lucas et al 2004) that would alter feeding behaviour and may improve growth.…”
Section: Growth Nutrition and Flesh Qualitymentioning
confidence: 99%
“…Human bias in the reproductive sequence of reared fish populations relative to the sequence in the wild is the most obvious cause, notably by removing the choice of sexual partners. Conversely, the reproductive behaviour of domesticated fish released in the wild causes relevant changes in some characteristics of the reproductive strategy (Pasquet 2019), which may also account for the modifications to mating performance during domestication.…”
Section: Reproductive Functionmentioning
confidence: 99%